2020
DOI: 10.1128/iai.00057-20
|View full text |Cite
|
Sign up to set email alerts
|

Endocervical miRNA Expression Profiles in Women Positive for Chlamydia trachomatis with Clinical Signs and/or Symptoms Are Distinct from Those in Women Positive for Chlamydia trachomatis without Signs and Symptoms

Abstract: Chlamydia trachomatis is the leading cause of sexual transmitted infections which may progress to pelvic inflammatory disease and infertility. No effective vaccine exists for Chlamydia, nor are there biomarkers available that readily predict disease progression. In this cross sectional, pilot study, we recruited symptomatic and asymptomatic women with C. trachomatis (CT) infection and asymptomatic, uninfected control women from an urban sexually transmitted disease clinic to determine if there were differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 22 publications
(32 reference statements)
0
2
0
Order By: Relevance
“…However, the possible modulation of host miRNAs by bacteria has not been so deeply explored until now that they could be considered as non-invasive and effective predictive biomarkers for complete spermatogenesis [30]. Only a single study on female patients reported modification of a specific endocervical miRNA pattern in patients with Chlamydia trachomatis while other studies on mouse models only hypothesized an association between different species of Chlamydia and specific host miRNAs in the female murine genital tract [43][44][45][46][47]. To our knowledge, no evidence reported a modulation of sperm miRNA by UP, and therefore this is a novel insight into exploring host miRNA modifications by bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…However, the possible modulation of host miRNAs by bacteria has not been so deeply explored until now that they could be considered as non-invasive and effective predictive biomarkers for complete spermatogenesis [30]. Only a single study on female patients reported modification of a specific endocervical miRNA pattern in patients with Chlamydia trachomatis while other studies on mouse models only hypothesized an association between different species of Chlamydia and specific host miRNAs in the female murine genital tract [43][44][45][46][47]. To our knowledge, no evidence reported a modulation of sperm miRNA by UP, and therefore this is a novel insight into exploring host miRNA modifications by bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…MiRNAs play a crucial role in the assessment of the effectiveness and prognosis of treatment for CT infection in the reproductive tract. Batteiger et al [43] examined samples from 83 symptomatic and asymptomatic CT-infected females and analyzed the diferences in miRNA expression. Compared to healthy individuals, in the symptomatic infection group, miRNA-142 and miRNA-147 showed a 2.2-6.9-fold increase in expression, while the asymptomatic infection group In vitro [27] miR-101-3p TLR2 3, UTR…”
Section: Role Of Mirnas In Genital Ct Infectionmentioning
confidence: 99%